Chronic obstructive pulmonary disease in severe mental illness: A timely diagnosis to advance the process of quitting smoking. Issue 1 (26th February 2021) - Jaen-Moreno, M. J.; Feu, N.; del Pozo, G. I.; Gómez, C.; Carrión, L.; Chauca, G. M.; Guler, I.; Montiel, F. J.; Sánchez, M.D.; Alcalá, J. A.; Gutierrez-Rojas, L.; Molina, V.; et al.
Abstract: Background: This study has two main objectives: to describe the prevalence of undetected chronic obstructive pulmonary disease (COPD) in a clinical sample of smokers with severe mental illness (SMI), and to assess the value of the Tobacco Intensive Motivational Estimated Risk tool, which informs smokers of their respiratory risk and uses brief text messages to reinforce intervention. Method: A multicenter, randomized, open-label, and active-controlled clinical trial, with a 12-month follow-up. Outpatients with schizophrenia (SZ) and bipolar disorder were randomized either to the experimental group—studied by spirometry and informed of their calculated lung age and degree of obstruction (if any)—or to the active control group, who followed the 5 A's intervention. Results: The study sample consisted of 160 patients (71.9% SZ), 78.1% of whom completed the 12-month follow-up. Of the patients who completed the spirometry test, 23.9% showed evidence of COPD (77.8% in moderate or severe stages). TIMER was associated with a significant reduction in tobacco use at week 12 and in the long term, 21.9% of patients reduced consumption and 14.6% at least halved it. At week 48, six patients (7.3%) allocated to the experimental group achieved the seven-day smoking abstinence confirmed by CO (primary outcome in terms of efficacy), compared to three (3.8%) in the control group. Conclusion: In this clinical pilot trial, one in four outpatients with an SMI who smoked had undiagnosed COPD. An intensive intervention tool favors the early detection of COPD and maintains its efficacy to quit smoking, compared with the standard 5 A's intervention.